Assessment to Low-cost Apartment in Sidoarjo District, East Java Province - Ria A.A. Soemitro; Farida Rachmawati (Institut Teknologi Sepuluh Nopember, 2017)
The low-cost apartment development program is one of the reliable solutions to reduce housing backlog in East Java Province due to land scarcity and high price of land. There are some supporting regulations concerning low-cost apartment management and implementation. But in some aspects, the regulation is not applicable. The objectives of this research are to compare the low-cost apartment regulation and real implementation in Sidoarjo and to generate improvement strategies. The regulation and technical standard variables were obtained from literature review studies. The comparison parameters to better understand the low-cost apartment implementation were then observed to purposive sampling respondents from management team and 60 random sampling respondents from inhabitants. These unconformity variables were then identified and analyzed using descriptive statistic. The result shows that some problems between regulation and real implementation are associated with rental price, inhabitant segmentation, maintenance program. Some strategies for the better implementation according to the inhabitant’s need and regulation are determine segmentation and limitation in rental period, scheduling the operation and maintenance periodically and list it in the planned cash flow, consider to create spesific institution to operate the low-cost apartment in order to overcome the finance system constraint and adjust more proper rental price.